Primary and secondary gait deviations of stroke survivors and their association with gait performance - Kim, H.-S.; Chung, S.-C.; Choi, M.-H.; Gim, S.-Y.; Kim, W.-R.; Tack, G.-R.; Lim, D.-W.; Chun, S.-K.; Kim, J.-W.; Mun, K.-R. (Society of Physical Therapy Science (Rigaku Ryoho Kagakugakkai), 2016)
[Purpose] Stroke survivors exhibit abnormal pelvic motion and significantly deteriorated gait performance. Although the gait of stroke survivors has been evaluated at the primary level pertaining to ankle, knee, and hip motions, secondary deviations involving the pelvic motions are strongly related to the primary level. Therefore, the aim of this study was to identify the kinematic differences of the primary and secondary joints and to identify mechanism differences that alter the gait performance of stroke survivors. [Subjects and Methods] Five healthy subjects and five stroke survivors were recruited. All the subjects were instructed to walk at a self-selected speed. The joint kinematics and gait parameters were calculated. [Results] For the stroke survivors, the range of motion of the primary-joint motions were significantly reduced, and the secondary-joint motions were significantly increased. Additionally, for the healthy subjects, the primary joint kinematics were the main factors ensuring gait performance, whereas for the stoke survivors, the secondary-joint motions were the main factors. [Conclusion] The results indicate that while increasing the range of motion of primary-joint movements is the main target to achieve, there is a strong need to constrain and support pelvic motions in order to improve the outcome of gait rehabilitation. ？ 2016 The Society of Physical Therapy Science. Published by IPEC Inc.